STUDI HANTARAN LISTRIK SENYAWA SRN+1TINO3N+1 (N = 1 DAN 2) FASA RUDDLESDEN-POPPER YANG DISINTESIS DENGAN METODE LELEHAN GARAM - Putri, Yulia Eka; Yusri, Hamsal; -, Zulhadjri (Universitas Andalas, 2015)
Srn+1TinO3n+1 (n = 1, 2,...n)Ruddlesden-Popper phase is a metal oxide compound with a layered structure consisting of SrTiO3 perovskite layers and strontium oxide (SrO) layers, thus this material has a potential as termoeletrik compounds that could be developed as an alternative material for renewable energy. In this study, we examine one of the 3 parameters of termoelectric properties, namely the electrical conductivity. Srn+1TinO3n+1 (n = 1 and 2)Ruddlesden-Popper phases were synthesized using molten salt method. The synthesis was carried out at 950 Â°C for 10 hours with a ratio of precursor and salt were 1: 0.5. Structural analysis by X-Ray Diffractometer (XRD) confirmed that all synthesized compounds formed Srn+1TinO3n+1 (n = 1, and 2) Ruddlesden-Popper phase with the characteristic peaks at 2q = 31o, 32o, and 46o. The morphology analysis by Scanning Electron Microscope (SEM) showed that the particles have plate-shaped with crystallites size were 20 nm. The electrical properties were measured using LCR meter with the highest electrical conductivity of 2.25x10-7 S / cm which showed the semiconductors behaviour.